Physical and engineering properties of BARI released three groundnut varieties - Hoque, MA (Bangladesh Journal of Agricultural Research, 2020)
The knowledge of the physical characteristics of particles is essential for the designer of agricultural machines. The study was aimed to determine physical and engineering properties of three selected varieties of groundnuts cultivated in Bangladesh such as Dhaka-1, BARI Badam-8 and BARI Badam-9 at safe storage moisture content of 7.5%. One hundred groundnut pods and kernels were randomly selected and the length, width and thickness were measured using a vernier caliper. The geometric mean diameter, sphericity, aspect ratio was calculated using standard formula and measured values. Bulk density, true density, mass and porosity were found through direct weighing and water displacement. Angle of repose of pods and kernels was also measured on wood, glass and mild steel sheet surfaces. BARI Badam-9 had the highest pod geometric mean diameter and BARI Badam-8 had the highest kernel geometric mean diameter. Sphericity of groundnut pod was the highest for Dhaka-1. Surface area of pod and aspect ratio of both pod and kernel were the highest in BARI Badam-9. Porosity of the pod was the least for BARI Badam-8. Angle of repose of kernel varied on wood and glass. But it was similar for kernel on MS sheet for the varieties. This result will be useful to design and develop groundnut processing equipment for different varietal variability Bangladesh J. Agril. Res. 44(4): 609-620, December 2019